Social security and health in colombia. current status of the reform (2000)
In this paper, an integral conception of social security within the socio-economic context of globalization and its political implications for developing societies is assumed. Although centered in the Colombian health sector reform, special reference is made to processes of social security reform around the world, pointing out differences with the less advanced and particularities in aspects concerning health. This conception starts from considering certain assumptions and misconceptions, which guided the processes in our nations, both of which can be better explained by the economic crisis of social security than by the rationality of social processes. Several evaluations and proposals, which have taken place in the five years following the implementation of the 1993 Law No. 100, are considered for the analysis. In conclusion, integration of the model based upon philosophical principles and the national Constitution with emphasis on those principles aimed at stimulating citizen welfare, decentralization, recovery of public health, legitimating of the reform before the people and regulatory simplification of the social security system is deemed necessary.